PENGARUH PERILAKU KONSUMEN DAN PROSES PSIKOLOGIS TERHADAP KEPUTUSAN PEMBELIAN : (STUDI PADA SALAH SATU JAJANAN KULINER DI KOTA BANDUNG) - Juhana , Dudung (Majalah Bisnis & IPTEK, 2013)
Deciding to buy is an essential aspect of a company’s business activities. The goal of this study is to determine the effect of consumer behavior and psychological processes on purchasing decisions. The research model uses the inferential approach by distributing questionnaires to consumers on a culinary spot in Bandung. The sampling technique of this study is the purposive sampling. This research uses multiple regression analysis to answer the research hypothesis. The results show there is a significant influence on consumer behavior and psychological processes on purchasing decisions. Keywords: consumer behavior, psychological processes, purchasing decisions.